The Effect of Sport Education on the Learning Motivation of Junior High School Students in Physical Education - Riki Ramadhan; Fauzan Effendy (Universitas Bengkulu, 2021)
In the learning process in physical education, motivation has a very important roles, because motivation determines student effort in the learning process in physical education. A learning model that can be felt to motivating is Sport Education. The purpose of this study was to examine the effect of Sport Education on student learning motivation in physical education. The research method uses a pre-experimental method using a intact-group design of 15 lessons. Participants in this study were 40 people who were drawn using the technique systematic sampling. The instrument uses a student learning motivation questionnaire in physical education. Data analysis techniques using descriptive statistics and independent samples t-test. The results of the study concluded that there were differences in the effect of Sport Education and traditional learning on the learning motivation of junior high school students in physical education. In order to carry out further research using the complete role in using Sport Education as an indication that Sport Education can be used as a new alternative in the 2013 curriculum that still on-going and can be adapted to project-based learning.